2014
DOI: 10.1038/emm.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 4 mediates lysophosphatidic acid-stimulated migration and proliferation of PC3M prostate cancer cells

Abstract: Prostate cancer is the most frequently diagnosed malignancy and the second leading cause of cancer mortality among men in the United States. Accumulating evidence suggests that lysophosphatidic acid (LPA) serves as an autocrine/paracrine mediator to affect initiation, progression and metastasis of prostate cancer. In the current study, we demonstrate that LPA stimulates migration and proliferation of highly metastatic human prostate cancer, PC-3M-luc-C6 cells. LPA-induced migration of PC-3M-luc-C6 cells was ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Moreover, KLF4 expression is markedly down-regulated in colon cancer, and the loss of KLF4 can serve as an independent predictor of its recurrence and survival [38]. However, KLF4 reportedly acts as an oncogene in melanoma and prostate cancer [39, 40]. The dual function of KLF4 in cancer biological behavior may shift depending on tumor type, tumor stage, and research approach.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KLF4 expression is markedly down-regulated in colon cancer, and the loss of KLF4 can serve as an independent predictor of its recurrence and survival [38]. However, KLF4 reportedly acts as an oncogene in melanoma and prostate cancer [39, 40]. The dual function of KLF4 in cancer biological behavior may shift depending on tumor type, tumor stage, and research approach.…”
Section: Discussionmentioning
confidence: 99%
“…As several reports have shown, ZNF750 interacts with KLF4 to induce differentiation genes [14,25,26] . KLF4 is a member of the Krüppel-type zinc finger transcription factor family [27][28][29] . Ma et al [30] reported that expression of KLF4 was negatively correlated with lymph node metastasis and stage of progression in ESCC cases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LINC00673 is overexpressed in both hepatocellular carcinoma and tongue squamous cell carcinoma (TSCC) and also associated with poor prognoses of these carcinomas. 12 DNA methylation is closely linked to numerous human cancers and KLF4, as readers of DNA methylation specific to sequence, also requires methylated cytosine-phosphate-guanine (CpG). 9 KLF4 belongs to the KLFs class of transcriptional mediators which can bind to DNA and are widely expressed in human cancers serving as oncogenes or tumour suppressors.…”
mentioning
confidence: 99%